PENGARUH PELATIHAN SOFT SKILL DAN KOMUNIKASI INTERPERSONAL TERHADAP KINERJA TIM - Verliyani Gowasa; Mukhamad Kholil Aswan (Media Bina Ilmiah, 2025)
This study aims to analyze the effect of soft skill training and interpersonal communication on team performance. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were collected through questionnaires distributed to 286 respondents and analyzed using the SPSS program. The results of the study showed that the research instrument was declared reliable with a Cronbach's Alpha value of each variable above 0.70. The results of the F test showed that soft skill training and interpersonal communication simultaneously had a significant effect on team performance (Sig. = 0.000). Partially, both variables also had a significant effect with a soft skill training regression coefficient of 0.464 and interpersonal communication of 0.685. This shows that interpersonal communication has a more dominant influence in improving team performance. The regression model obtained is: Y = 1.924 + 0.464X₁ + 0.685X₂. This study provides implications that companies need to pay more attention to the development of soft skills and interpersonal communication in order to improve the effectiveness of teamwork. Further research is recommended to add other variables such as leadership style and work environment to obtain a more comprehensive picture.